Preliminary study on efficiency of arsenic filter from kaolin for water for consumption - Sinthusarn, Apaporn; Bunyovimonnat, Nongluk; Chuasuwan, Aungsana; Krongpong, Mathee (Bulletin of Applied Sciences, 2022)
This research is a preliminary study on "Kaolin”, a natural raw material, which is found in many parts of Thailand, in order to apply as a water filter for arsenic removal in water for consumption instead of activated alumina, which is quite expensive and must be imported from abroad. Chemical structure of Kaolin is aluminosilicate (AL203.2SIO2.2H20; 39.5 : 46.5 : 14). Its properties are white before burning and after calcination, high fire resistance. When activated with heat, Kaolin has the ability to capture anions in water based on the pH value of the water. Results of the study on the efficiency of the filter were showed that the filter was suitable for the removal of arsenic in water prepared in the laboratory. The filter formula 1 (100% Kaolin), calcined at condition 1 (at 200 °C for 1 hour, 400 °C for 1 hour, and 600 °C for 3 hours, respectively) was the best condition for arsenic adsorption. The efficiency of arsenic adsorption depends on quantity and height of the adsorbent in the filter. The 3.5 liters of the produced filter can be regenerated with 0.1N. Sodium hydroxide, and 0.1N. Hydrochloric acid, respectively, up to 3 times, and this can produce water for consumption within the criteria of drinking water (arsenic not more than 0.01 mg/l) for 400 liters. Therefore this preliminary study can be a guideline for conducting research on using Kaolin to produce a natural filter for arsenic removal for potable water purifier in the future.